2011
DOI: 10.1002/smr.483
|View full text |Cite
|
Sign up to set email alerts
|

Agile methods and organizational culture: reflections about cultural levels

Abstract: Agile methods emerge as an alternative to improve quality and performance in software development processes. However, as agile methods are essentially focused on human aspects, their application in companies depends mostly on their adequacy to the current organizational culture. This study explores the view of the organizational culture in three levels as a theoretical framework to allow early detection of problems, which could jeopardize the adoption of agile methods by a company. This article points out that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 7 publications
0
31
0
7
Order By: Relevance
“…Conboy et al [28] explained the role of the people in Agile migration and emphasized that without people interest, processes cannot change well. Tolfo et al [10] by describing cultural issues and human aspects of Agile migration, emphasized that commitment of people to change process is necessary for moving to Agile. Sureshchandra and Shrinivasavadhani [29] explained that unhappy people make transformation so hard.…”
Section: Getting People Buy-inmentioning
confidence: 99%
See 1 more Smart Citation
“…Conboy et al [28] explained the role of the people in Agile migration and emphasized that without people interest, processes cannot change well. Tolfo et al [10] by describing cultural issues and human aspects of Agile migration, emphasized that commitment of people to change process is necessary for moving to Agile. Sureshchandra and Shrinivasavadhani [29] explained that unhappy people make transformation so hard.…”
Section: Getting People Buy-inmentioning
confidence: 99%
“…This reveals that most often software companies start ATP without providing the required prerequisites. Since ATP comprises all practices and activities required to change the development process, the scope and type of its prerequisites vary from technical to social aspects of the transition process [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Four agile development papers were related to organizational culture. One showed that specific organizational cultures correlates with effective use agile methods [56] and three of the papers the relationship were discussed, and obstacles and facilitators were identified [23,60,18]. Multi concept studies: Five studies investigated the relationship to software process improvement (SPI).…”
Section: Organizationmentioning
confidence: 99%
“…Among them, it seemed that cultural problems are more critical than the others since they were addressed by almost all of the participants. In several studies people and organizational culture are discussed [5,9,14]. Cockburn et al, by describing role of the people in moving to Agile methods mentioned that people's culture strongly influences transformation process [3].…”
Section: Impediments To Changementioning
confidence: 99%